Overview of Knowledge about Basic Life Support (BLS) for Nature Lovers Students - Resti Hardianti Ali; Andi Sakurawati; Tuthanurani Nachrawy (Indonesian Journal of Global Health Research, 2025)
Basic life support (BLS), comprising cardiovascular resuscitation and automated external defibrillator use, is not exclusively taught to health care workers but also to layman. BLS could save the lives of trauma and/or other emergency patients, particularly where health care facility is unreachable. Students’ mountaineering club members particularly are under constant risks of these conditions. There has been no study regarding BLS knowledge profile in North Maluku, especially among students’ mountaineering club members. Objective: To describe the level of knowledge about BLS among students’ mountaineering club members at Khairun University. Methods: This observational, descriptive, cross-sectional descriptive study was conducted on all students’ mountaineering club members at Khairun University in 2022. Analysis was performed using univariate analysis. Results: Among 123 respondents from 14 study programs, most were male (57,7%), were civil engineering students (22,2%), and had previous BLS training (87,8%). Regarding the level of BLS knowledge, 6,5% had good knowledge, 50,4% mediocre, and 43,1%had low level of knowledge. Conclusion: Most students’ mountaineering club members at Khairun University had mediocre level of knowledge regarding BLS. Further study is required to confirm this finding.